IMPLEMENTASI GREEN ECONOMY TERHADAP ECONOMY PEMBANGUNAN BERKELANJUTAN DI KOTA KUPANG - Daflora Ventiana Suryawati; Fransina W. Ballo (E-Jurnal Ekonomi Pembangunan, 2024)
The city of Kupang is a city located in the province of East Nusa Tenggara and is the capital of the province of NTT. In addition, the city of Kupang is also a student city in NTT, so this indicates that the population density in the city of Kupang is increasing every year and resulting in increased economic activity. and this condition encourages increased waste production in Kupang City. The purpose of this research is to explain the implementation of Green Economy for Sustainable Development in Kupang City and also to explain how the people of Kupang City understand waste as a public issue. This study uses a descriptive qualitative method. The results of this study are recommended to the people of Kupang City, the government and also to the author Keywords: Green Economy, Sustainable Development.